Design of test track for accurate calibration of two wheel differential mobile robots - Jung, Changbae; Moon, Chang-bae; Jung, Daun; Choi, JongSuk; Chung, Woojin (KOREAN SOC PRECISION ENG, 2014)
Odometry using incremental wheel encoder sensors provides the relative position of a mobile robot. The major drawback of odometry is the accumulation of kinematic modeling errors when travel distance increases. The major systematic error sources are unequal wheel diameters and erroneous wheelbase. The UMBmark test is a practical and useful calibration scheme for systematic odometry errors of two wheel differential mobile robots. We previously proposed an accurate calibration scheme that extends the conventional UMBmark. A calibration experiment was carried out using the robot's heading errors, and kinematic parameters were derived by considering the coupled effect of the systematic errors on a test track. In this paper, we propose design guidelines of test tracks for odometry calibration. As non-systematic errors constitute a grave problem in practical applications, the test track shape and size should be determined by considering the distributions of systematic and non-systematic errors. Numerical simulations and experiments clearly demonstrate that the proposed scheme results in more accurate calibration results.